The role of anti-variable surface glycoprotein antibody responses in bovine trypanotolerance - Williams, D.J.L.; Taylor, K.; Newson, J.; Gichuki, B.; Naessens, Jan (Wiley, 1996)
It has been reported that some breeds of cattle such as the N'Dama mount a more effective antibody response to the variable surface glycoprotein coat of trypanosomes and that this may contribute to their ability to control the infection. Thus we have investigated antibody responses to surface exposed epitopes of the variable surface glycoprotein in Trypanosoma congolense-infected N'Dama (trypanotolerant) and Boran (susceptible) cattle. Similar titres and isotypes were found in both N'Damas and Borans indicating that trypanotolerance is not associated with superior antibody-mediated destruction of trypanosomes. However, significant differences in antibody responses to cryptic VSG epitopes and non-trypanosome antigens were identified. Trypanosusceptible Boran cattle had low IgG1 responses to cryptic epitopes but high IgM responses to non-trypanosome antigens such as 3-galactosidase. In contrast the N'Dama cattle had significantly higher IgG1 responses to cryptic VSG epitopes and negligible responses to 3-galactosidase. These results indicate differences in the induction of anti-trypanosome immune responses between trypanotolerant and susceptible cattle infected with T. congolense.